An overview of Shari'ah issues regarding the application of the Islamic letter of credit practice in Malaysia - Othman, Ahmad Azam; Che Hashim, Rosmawani; Abdul Aziz, Akhtarzaitie (International Shari'ah Research Academy for Islamic Finance (ISRA), 2010)
The Letter of Credit (LC) serves as an instrument of payment in international trade. Its aim is to facilitate trade between seller and buyer in different countries. To date, the Islamic banking environment promotes the use of the Islamic LC as a method of financing in international trade, particularly to Muslims and to the general public as a whole. Thus far, this facility is offered not only by Islamic banks, but also by all commercial banks. It is basically governed by the same rules of the UCP 600 that regulate the conventional LC. Realising the peculiarity in the application of this conventional rule to the Islamic LC, this paper focuses on the aim of harmonising the practice of the Islamic LC with the requirements of Shari'ah principles where elements such as interest (riba) and uncertainty (gharar) are prohibited. It begins by giving the background of the Islamic LC in Malaysia. Next, it discusses the definition and types of Islamic LCs, murabahah (cost-plus sale), wakalah (agency) and musharakah (partnership), as the issuance of the Islamic LC is based on these three concepts. In addition, it highlights comparisons between these three concepts. Furthermore, the focal point of discussion is on Shari'ah issues in the practice of the Islamic LC, such as governing rule, subject-matter, interest, INCOTERMS and insurance, contract ('aqd), discrepancy fee, and exclusion of risk of goods in the Islamic LC. Discussion of these issues leads us to identify whether they are in compliance with Shari'ah principles. In relation to this, various proposals are suggested to harmonise the rules applicable to the Islamic LC and Shari'ah principles.